Не просто коллега - Черниенко, Ю.А. (Материалы по археологии Северного Причерноморья, 2019)
The author was lucky to be familiar during 39 years with Vladislav Grigorievich Petrenko – a qualified specialist in the field of the Eneolithic and Early Bronze Age archeology, especially in the Usatovo culture, conscientious, decent, noble, responsive, cultural, in fine, intelligent and bright man. We worked together for a long time in the Archaeological Museum of Odessa, in expeditions. Vladislav also contributed to the study of the Middle and Late Bronze Age, especially of the settlement Voronovka II. He played notable role in my archaeological fate. I often felt the friendly support of Vlad. The researcher was distinguished by conscientiousness, purposefulness, love and disinterested devotion to his work. Some doctors of historical sciences can envy the talent, professionalism, erudition of V.G. Petrenko as a scientist, although he did not defend the dissertation on which he worked under the guidance of the well-known archaeologist E.K.Chernysh. The light memory about Vladislav Grigorievich Petrenko, the Archaeologist and Man, will remain forever in our hearts.